2021
DOI: 10.1093/asjof/ojab002
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Effect of Intravenous and Topical Tranexamic Acid in Liposuction: A Randomized Double-Blinded Controlled Trial

Abstract: Background Tranexamic acid (TXA) use in surgical procedures due to its hemostatic effects has been gaining an increased interest. In plastic surgery, the effects of TXA have been studied intravenously (IV), and there have been some reports regarding local use. Objectives A comparative study examining the combined effect of IV and local TXA was conducted. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 23 publications
(25 reference statements)
0
13
0
1
Order By: Relevance
“…A few randomized controlled trials have also evaluated the efficacy of TXA in reduction mammaplasty. A study by Abboud et al 33 found efficacy for the use of combined IVand local TXA in reducing blood loss for patients undergoing reduction mammaplasty with liposuction. Two randomized controlled trials by Ausen et al 28,29 found topical TXA to be effective at reducing drain fluid production and blood loss but found no difference in postoperative pain scores or complications.…”
Section: Discussionmentioning
confidence: 99%
“…A few randomized controlled trials have also evaluated the efficacy of TXA in reduction mammaplasty. A study by Abboud et al 33 found efficacy for the use of combined IVand local TXA in reducing blood loss for patients undergoing reduction mammaplasty with liposuction. Two randomized controlled trials by Ausen et al 28,29 found topical TXA to be effective at reducing drain fluid production and blood loss but found no difference in postoperative pain scores or complications.…”
Section: Discussionmentioning
confidence: 99%
“…Die Arbeit von Abboud et al 2020 beschreibt eine kombinierte Anwendung von Tranexamsäure intravenös und topisch bei einer Mammareduktionsplastik mit konturangleichender Liposuktion, welche in einer randomisierten doppelt-blinden Kontrollstudie untersucht wurde. Die Autoren stellten fest, dass das Blutvolumen im Aspirat sowie in den Drainagen in der Gruppe mit Tranexamsäure um 38% reduziert werden konnte 26 .…”
Section: Ergebnisseunclassified
“…Previous studies have found similar results in various procedures showing the effects of TXA in improving hemostasis. [40][41][42][43] In this study, low dose TXA demonstrates lower rates of complications and provides efficacy for hemostasis during craniosynostosis surgery. However, at this time, further research is required to reduce the uncertainty given study heterogeneity for recommendations to be provided.…”
Section: High Dosementioning
confidence: 99%